2018
DOI: 10.1002/mnfr.201700879
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenols Mitigate Gliadin‐Mediated Inflammation and Permeability in Vitro

Abstract: There are potential beneficial effects of GTE as an adjuvant therapy for celiac disease through direct interaction between gliadin proteins and green tea polyphenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…Within the category of flavonoids, anthocyanidins, flavan-3-ols and flavonols were the most studied in relation to their binding capacity to gluten proteins [ 26 , 27 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 ] ( Table 1 ). The interaction of gluten and its individual fractions with anthocyans was studied mainly by spectroscopic techniques, including ultraviolet–visible (UV-Vis), nuclear magnetic resonance (NMR), infrared (IR) and Raman spectroscopy [ 31 , 32 , 34 , 35 ].…”
Section: Polyphenols-gluten Interaction: Sequestering Of Celiac-rementioning
confidence: 99%
See 4 more Smart Citations
“…Within the category of flavonoids, anthocyanidins, flavan-3-ols and flavonols were the most studied in relation to their binding capacity to gluten proteins [ 26 , 27 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 ] ( Table 1 ). The interaction of gluten and its individual fractions with anthocyans was studied mainly by spectroscopic techniques, including ultraviolet–visible (UV-Vis), nuclear magnetic resonance (NMR), infrared (IR) and Raman spectroscopy [ 31 , 32 , 34 , 35 ].…”
Section: Polyphenols-gluten Interaction: Sequestering Of Celiac-rementioning
confidence: 99%
“…This knowledge about the pathogenesis of celiac disease allows different therapeutic approaches or approaches aimed at controlling or modulating certain processes ( Figure 2 ). A green tea extract containing mostly EGCG, inhibited pepsin/trypsin-mediated digestion of gliadins in vitro [ 36 ]. Moreover, enzyme activity assays showed that green tea extract was also able to inhibit pepsin and trypsin activity in a dose-dependent manner.…”
Section: Potential Translational Effects For Celiac Diseasementioning
confidence: 99%
See 3 more Smart Citations